The role of shallow and deep circulations in the Tropical Pacific Ocean heat budget - Navarro-Labastida, René Gabriel; Farneti, Riccardo (Frontiers in Marine Science, 2023)
The Tropical Pacific Ocean plays an important role in setting the global ocean heat content and redistribution. We examined the role of the shallow and deep circulations in the tropical Pacific in unperturbed and transient climate change conditions in a global ocean model. We found that, in the Control state, the shallow circulation is by far the largest contributor to the overall balance of the column, where the balance is set as the residual between advective cooling and warming by vertical diffusive mixing. Subject to surface flux perturbations, changes in the tropical Pacific ocean heat budget can be explained by shallow wind-driven overturning circulation changes. For wind stress anomalies, the shallow ocean heat budget imbalance is directly related to overturning circulation changes, whereas under heat flux perturbations warming of the shallow ocean is related to strengthened mid-latitude subduction and weakened dense water production at higher latitudes.